2020
DOI: 10.1111/iwj.13282
|View full text |Cite
|
Sign up to set email alerts
|

Does obesity impact the outcome of severely burned patients?

Abstract: Although obesity appears to be an important predictor of mortality and morbidity, little data about the impact of body mass index (BMI) on the outcome of severely burned patients are available. Patients admitted to the General Hospital Vienna between 1994 and 2014, who underwent surgery because of burn injuries, were enrolled in this study. BMI was used to divide patients into five groups: BMI 18.5 to 24.9, 25 to 29.9, 30 to 34.9, 35 to 39.9, and > 40. The groups were compared in terms of difference of mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…There were 18 studies 89,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143] (1,415,697 participants) with critically ill populations (Table S3): quadratic term for mean BMI with a linear term (Table 2) or when groups with mean BMIs <20 kg/m 2 were excluded. The interaction terms for Asian/non-Asian majority countries were non-significant.…”
Section: Critically Ill Populationsmentioning
confidence: 99%
“…There were 18 studies 89,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143] (1,415,697 participants) with critically ill populations (Table S3): quadratic term for mean BMI with a linear term (Table 2) or when groups with mean BMIs <20 kg/m 2 were excluded. The interaction terms for Asian/non-Asian majority countries were non-significant.…”
Section: Critically Ill Populationsmentioning
confidence: 99%
“…Owing to the retrospective study design, the basis for data regarding psychiatric illnesses are poor and their potential impact on the long‐term outcome was not evaluated, which can be seen as a limitation. In a previously conducted study at our department, authors have shown that body mass index could not be confirmed as an independent risk factor for severely burned patients 24 . However, we have seen that obesity in burn patients can have a protective effect against mortality and provide a better outcome in the aging population.…”
Section: Discussionmentioning
confidence: 59%
“…In a previously conducted study at our department, authors have shown that body mass index could not be confirmed as an independent risk factor for severely burned patients. 24 However, we have seen that obesity in burn patients can have a protective effect against mortality and provide a better outcome in the aging population. Furthermore, this paper described gender-specific patterns in patients ≥75 years that required intensive care after the procedure for plastic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Still, obesity was significantly associated with longer LoS and increased comorbid illness. Recent studies are implemented on larger populations, with different subgroups, and have considered the etiological context (20,23). A recent dose-response meta-analysis on the effect of BMI on the mortality of ICUadmitted patients showed that for each unit of increase in BMI, a 0.6% decrease in mortality rate is expected (24).…”
Section: Discussionmentioning
confidence: 99%